A modified oblique lumbar interbody fusion: A better way to establish an exposure under direct microscopic vision - Wang, Kai; Zhang, Xiangyu; Zhao, Zirun; Chou, Dean; Jian, Fengzeng; Wu, Hao (Frontiers in Surgery, 2023)
Study Design: This is a retrospective study. Objective: To demonstrate a modified oblique lumbar interbody fusion (OILF) technique for L1-L5. Methods: The modified technique splits anterior portion of psoas belly to access the oblique corridor (OC) anteroinferior to psoas, minimizing psoas manipulation and retraction and avoiding nerve injury while offering excellent microscopic visualization. Psoas weakness and neurovascular complication rates in patients treated with traditional OLIF (T-OLIF) or anteroinferior psoas OLIF (AP-OLIF) were retrospectively reviewed. Clinical outcomes were also reviewed. Results: A total of 162 cases treated with T-OLIF (n = 73) and AP-OLIF (n = 89) for degenerative lumbar disease were included. The mean operative time and blood loss were less with AP-OLIF (P<0.01). Approach related complications were 14 (19.1%) with T-OLIF and 4 (4.5%) with AP-OLIF. Postoperative visual analog scale (VAS) and Oswestry Disability Index (ODI) scores improved in both T-OIF and AP-OIF groups (P<0.01). Conclusion: The modified OLIF technique (AP-OLIF) is characterized by an easy exposure of the lumbar spine under direct microscopic vision, resulting in less psoas weakness and neurovascular injury.